Aldo Mieli e il fascismo - Abbri, Ferdinando (Chimica nella Scuola, 2022)
Aldo Mieli (1879 - 1950), a chemist from Leghorn, is internationally well-known as one of the pioneers of the contemporary history of science. Jew, homosexual, and socialist in his youth, he was obliged to cope with the tragic, historical events of the first half of the Twentieth century. From Italy he was obliged to take refuge abroad, first in France, then in Argentina. The paper focuses on Mieli’s relationships with Italian Fascism, which were marked by illusions, political naivety, mistaken expectations, but in Argentina Mieli could make public his radical opposition to Fascism and Nazism.